2021
DOI: 10.3389/fmicb.2021.654783
|View full text |Cite|
|
Sign up to set email alerts
|

Reactive Oxygen Species-Related Ceftazidime Resistance Is Caused by the Pyruvate Cycle Perturbation and Reverted by Fe3 + in Edwardsiella tarda

Abstract: Reactive oxygen species (ROS) are related to antibiotic resistance and have been reported in bacteria. However, whether ROS contribute to ceftazidime resistance and plays a role in ceftazidime-mediated killing is unknown. The present study showed lower ROS production in ceftazidime-resistant Edwardsiella tarda (LTB4-RCAZ) than that in LTB4-sensitive E. tarda (LTB4-S), two isogenic E. tarda LTB4 strains, which was related to bacterial viability in the presence of ceftazidime. Consistently, ROS promoter Fe3+ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Interestingly, the major flux is from phosphoenolpyruvate to pyruvate to AcCoA, with appreciable amount of carbon going to oxalacetate from pyruvate ( Kohlstedt and Wittmann, 2019 ), which is consistent with oxaloacetate instead of AcCoA as a fuel for the P cycle ( Su et al, 2018 ). The repressed P cycle (including the TCA cycle) is related to antibiotic resistance and has been reported in some bacteria including Vibrio alginolyticus , Edwardsiella tarda , and Stenotrophomonas maltophilia ( Cheng et al, 2018 ; Gil-Gil et al, 2020 ; Li et al, 2020 ; Su et al, 2020 ; Ye et al, 2021 ). Our recent report shows that the P cycle is downregulated ( Kuang et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the major flux is from phosphoenolpyruvate to pyruvate to AcCoA, with appreciable amount of carbon going to oxalacetate from pyruvate ( Kohlstedt and Wittmann, 2019 ), which is consistent with oxaloacetate instead of AcCoA as a fuel for the P cycle ( Su et al, 2018 ). The repressed P cycle (including the TCA cycle) is related to antibiotic resistance and has been reported in some bacteria including Vibrio alginolyticus , Edwardsiella tarda , and Stenotrophomonas maltophilia ( Cheng et al, 2018 ; Gil-Gil et al, 2020 ; Li et al, 2020 ; Su et al, 2020 ; Ye et al, 2021 ). Our recent report shows that the P cycle is downregulated ( Kuang et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to observe that increased fatty acid biosynthesis promotes bacterial growth during antibiotic stress. The increase in fatty acid biosynthesis might be a strategy deployed by bacteria to maintain the membrane integrity as the membrane could be disrupted by antibiotic-induced ROS ( Konai and Haldar, 2017 ; Ye et al, 2021 ). The altered transcription of fatty acid biosynthesis might be attributed to the antibiotic effect that reduces the transcription and translation of lipoproteins supporting cell membrane structure ( Braun and Hantke, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As described above, the siderophore catechol moiety on the C-3 side chain of CFDC chelated Fe 3+ into cells, and Fe 3+ was rapidly reduced to Fe 2+ by ferric reductase; thus, Fe 3+ overload promoted increased levels of Fe 2+ , and the Dps protein of E. coli could store elevated Fe 2+ with H 2 O 2 as the oxidant ( 42 , 43 ). Furthermore, the latest study reported that Fe 3+ could elevate ROS production by promoting the pyruvate cycle ( 44 ). In this study, we also identified the same results ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ROS stress induced by sublethal concentrations of antibiotics can lead to multidrug resistance ( 49 , 50 ). Notably, Ye et al reported that CAZ-induced ROS production was required for CAZ-mediated killing in ceftazidime-resistant Edwardsiella tarda (LTB4-R CAZ ), and a reduction in ROS production contributed to E. tarda resistance to CAZ ( 44 ). In our work, we demonstrated that CFDC confers stronger ROS stress than CPM and CAZ, and knockout of NADH-quinone oxidoreductase genes ( nuoA , nuoC , nuoE , nuoF , nuoG , nuoJ , nuoL , nuoM ) in the respiratory chain promoted insensitivity of E. coli to CFDC far beyond the effects of CPM and CAZ.…”
Section: Discussionmentioning
confidence: 99%